Additions to the annotated list of marine alien biota in the Mediterranean with special emphasis on Foraminifera and Parasites - ZENETOS, A.; MERIC, E.; VERLAQUE, M.; GALLI, P.; BOUDOURESQUE, C.F.; GIANGRANDE, A.; CINAR, M.E.; BILECENOGLU, M. (Mediterranean Marine Science, 2008)
The present work is an update of the annotated list (ZENETOS et al., 2006) based on literature up to April 2008. Emphasis is given to ecofunctional/taxonomic groups poorly addressed in the annotated list, such as the foraminiferan and parasites, while macrophytes are critically reviewed following the CIESM Atlas (VERLAQUE et al., in press). Moreover, in this update the bio-geographic area addressed includes the Sea of Marmara. The update yields a further 175 alien species in the Mediterranean bringing the total to 903. As evidenced by recent findings, more and more previously known ‘casual’ aliens, are becoming established. Approximately 100 more species have become well established in the region, raising the number of established species to 496 versus 385 until 2005. In the period from January 2006 to April 2008 more than 80 published papers have resulted in the recording of 94 new aliens, which is interpreted as a new introduction every 9 days, a rate beyond the worst scenario.